Pengaruh Penggunaan Media Wordwall Terhadap Keaktifan dan Pemahaman Rantai Makanan Siswa Kelas V di UPTD SD Negeri Kebun 1 Kamal - Rahmawati, Titik; Kusmiyati (Citra Dharma Cindekia, 2024)
This study aims to analyze the impact of using the wordwall media on the activity and understanding of fifth-grade students regarding food chains. The wordwall media is a visual learning tool that can enhance student interaction and engagement in the learning process. The research method used is quantitative with an experimental design. The subjects of the study consist of 30 fifth-grade students divided into two groups: an experimental group that uses wordwall media and a control group that learns without the media.Data collection was conducted through pre-tests and post-tests to measure students' understanding of food chains, as well as questionnaires to assess student activity during the learning process. The analysis results show that the average post-test scores of the experimental group increased significantly compared to the control group, with p < 0.05. Additionally, 85% of students in the experimental group reported that they felt more active and engaged in the learning process. This study concludes that the use of wordwall media can significantly improve student activity and understanding of food chains, thus having a positive implication for teaching strategies in the classroom.